2022
DOI: 10.1007/s10840-022-01182-4
|View full text |Cite
|
Sign up to set email alerts
|

Ablation index-guided cavotricuspid isthmus ablation with contiguous lesions using fluoroscopy integrated 3D mapping in atrial flutter

Abstract: Purpose The feasibility and safety of cavotricuspid isthmus (CTI) ablation with contiguous lesions using ablation index (AI) under the guidance of fluoroscopy integrated 3D mapping (CARTO UNIVU/CU) in typical atrial flutter (AFL) remains uncertain. This study aimed to determine the efficacy of AI-guided CTI ablation with contiguous lesions in patients with AFL. Methods In this single-center, prospective, non-randomized, single-arm, observational study, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The findings indicated that the impact of all three parameters was comparable and did not significantly contribute to the inter-group differences, except for that on fluoroscopy time [ 19 ]. In their included studies, a study involving AI showed a significant reduction in fluoroscopy time among the intervention group [ 20 ]. However, the results from the other subgroups and the overall analysis did not show a statistically significant difference [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that the impact of all three parameters was comparable and did not significantly contribute to the inter-group differences, except for that on fluoroscopy time [ 19 ]. In their included studies, a study involving AI showed a significant reduction in fluoroscopy time among the intervention group [ 20 ]. However, the results from the other subgroups and the overall analysis did not show a statistically significant difference [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 Sakama et al studied CTI ablation in patients with AFL using ablation under the guidance of the CARTO-UNIVU™ module and demonstrated a shorter FT (0.2 ± 0.4 vs 1.7 ± 2.0 min, p < 0.001) and shorter RF time (4.2 ± 2.4 vs 5.1 ± 2.5 min, p = 0.011). 17 Moreover, Sommer et al demonstrated a significant learning effect associated with using this technology and reported a significant decrease in FT and FD with the operator's familiarity with the technology. Concretely, when comparing the first 50 cases with the last 50 cases, the FT reduced from 6.0 to 1.1 minutes, and FD reduced from 2,363 to 490 (p < 0.001 for both).…”
Section: Discussionmentioning
confidence: 99%